Availability of Physical Facilities and Teachers' Job Performance in Public Secondary Schools in Osun State, Nigeria - Ayotunde Samuel Akinwale; Bilikisu Oluwakemi Olaolu; Elijah Olusogo Sunday (Educational Considerations, 2025)
The study assessed how available physical facilities were in public secondary schools in Osun State. The study also investigated the level of job performance of teachers in the study area. The study further determined the relationship between availability of physical facilities and teachers' job performance in the study area. The design for the study was descriptive survey research design. The study’s population comprised all teachers and principals of public secondary schools in Osun East Senatorial District of the State. The study’s sample comprised 300 teachers and 60 school principals. Two local governments were selected from Ife zone of the district while four local governments were selected from Ilesa zone of the district using proportionate sampling technique. From each of the local governments selected, 10 public secondary schools were selected using simple random sampling technique. From each of the schools selected, five teachers and the school principal were selected using the purposive sampling technique. The instruments were Physical Facilities Availability and Teachers' Job Performance Questionnaire for Principals (PFATJPQP) and Physical Facilities Availability and Teachers' Job Performance Questionnaire for Teachers (PFATJPQT). Data collected were analysed using percentages and Pearson’ Product Moment Correlation. The results showed that physical facilities that were moderate in availability were a staffroom, classrooms with furniture, writing materials, water supply, laboratory and laboratory apparatus, and toilets. The facilities that were found to be unavailable were a library, technical workshops, fire extinguishers, school bus, music studio, and others. The study also revealed that the level of teachers’ job performance was moderate (49.2%). Furthermore, it was found that availability of physical facilities had a significant relationship with teachers’ job performance. The study recommended that more educational facilities should be made available in schools in order to increase teachers’ job performance and commitment.
Keywords: Facilities; physical facilities; job performance; teachers’ job performance